INVENTARISASI TUMBUHAN PAKU (Pteridophyta) DI HUTAN WISATA BULUH CINA SEBAGAI RANCANGAN HANDOUT BIOLOGI SMA - Mila Sri Yulia Ningsih; Yuslim Fauziah; Wan Syafi`i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to find out the types of ferns (Pteridophyta) in Buluh Chinese tourist forest and the design of bology learning handouts for class X SMA, held in December 2018 until January 2019. Determination of the location of the study was carried out using purposive sampling technique based on the presence of ferns in Buluh Cina tourist forest area on the seven research lakes. Based on observations on the seven lakes in Buluh China tourist forest, the District of Siak Hulu Kampar Regency has 24 species of ferns consisting of 3 classes, 8 orders, 13 families. The most found class of ferns is Pteropsida (true nail) with a total of 20 species, while the class Lycopsida (wire nail) only found 3 species, namely Lycopodium cernuum, Lygodium circinnatum, Lygodium microphylum and the least species are the Psilopsida (ancient Nail) Cyanthea contaminans. Environmental factors such as temperature; light intensity, humidity, soil pH suitable for the growth of ferns. The fern inventory produces a class X high school biology learning handout.Key Words: Fern, Tourism Forest, Inventory, Environmental factors